Evolution of nodal and nodal‐related genes and the putative composition of the heterodimers that trigger the nodal pathway in vertebrates. Issue 4 (17th June 2019) - Opazo, Juan C.; Kuraku, Shigehiro; Zavala, Kattina; Toloza‐Villalobos, Jessica; Hoffmann, Federico G.
Abstract: Nodal is a signaling molecule that belongs to the transforming growth factor‐β superfamily that plays key roles during the early stages of development of animals. In vertebrates Nodal forms an heterodimer with a GDF1/3 protein to activate the Nodal pathway. Vertebrates have a paralog of nodal in their genomes labeled Nodal‐related, but the evolutionary history of these genes is a matter of debate, mainly because of the presence of a variable numbers of genes in the vertebrate genomes sequenced so far. Thus, the goal of this study was to investigate the evolutionary history of the Nodal and Nodal‐related genes with an emphasis in tracking changes in the number of genes among vertebrates. Our results show the presence of two gene lineages (Nodal and Nodal‐related) that can be traced back to the ancestor of jawed vertebrates. These lineages have undergone processes of differential retention and lineage‐specific expansions. Our results imply that Nodal and Nodal‐related duplicated at the latest in the ancestor of gnathostomes, and they still retain a significant level of functional redundancy. By comparing the evolution of the Nodal/Nodal‐related with GDF1/3 gene family, it is possible to infer that there are several types of heterodimers that can trigger the Nodal pathway among vertebrates. Abstract : Phyletic distribution of Nodal, Nodal‐related, GDF1/3, GDF1, and GDF3 genes among vertebrates, including the putative composition of the heterodimer. HIGHLIGHTS: The Nodal and Nodal‐related genes can be traced back to the ancestor of jawed vertebrates. The Nodal and Nodal‐related genes have been differentially retained. Several types of heterodimers can trigger the Nodal pathway among vertebrates.